הגאוגרפיה של הבדיון: עיון בספרות היהודית המודרנית 1920-1860 - נתנאל לילך (מכאן, 2022)
This article offers a reading in fictional representations of sites, landscapes and surroundings in modern Hebrew and Yiddish fiction. Its main interrogation concerns the map of Jewish fiction during the second half of the 19th century, starting with the literary works of Israel Aksenfeld, Yehuda Leib Gordon and Shalom Yaakov Abramowitz in the 1860s, and ending in the 1920s with the post-war literature of Gershon Shoffman and others. Presenting a description of the geography of Jewish fiction in an age of historical and political instability, the article introduces the term “geography of fiction” to refer to the l representation of homelands and wanderings in a selection of modern Jewish fiction. This geography includes the invented descriptions, code names and biblical references this fiction uses to name and characterize the various sites and trajectories on the map.